FRACTAL NATURE OF LATERAL STRUCTURES IN GEOSYSTEMS - Vasilyev L.N.; Tyuflin A.S. (My University, 1990)
The concept of a lateral structure of geosystems is most useful in identification of the nature of land use. The properties of lateral structures that exhibit signs of disorder can be determined in terms of fractals. Fractal geometry gives a quantitative expression to randomness and thus can be used to describe the lateral structures of land use, river and erosion networks, and relief forms by using the dimensionality of self-similarity. Our investigation had two objectives: 1) to establish the existence of fractal properties of lateral structures, and (2) to give a geometric interpretation of their fractal dimensions. Our investigation indicates that agricultural geosystems have a fractal nature whose dimensionality is conveniently used for the lateral differentiation of land use systems.